What is the relationship of stress to patients’ kidney stone-related quality of life? - Lundeen, Colin; Lim, Jonathan R.Z.; Scotland, Kymora B.; Ardekani, Reza Safaee; Penniston, Kristina L.; Streeper, Necole M.; Chi, Thomas; Landman, Jaime; Viprakasit, Davis P.; Chew, Ben H. (Canadian Urological Association Journal, 2020)
Introduction: Health-related quality of life (HRQOL) is decreased in patients with kidney stones at all stages of stone disease, even when asymptomatic. Stress is thought to contribute to HRQOL, although there has been minimal investigation into the effect of stress on stone-related quality of life (QOL). We used the Wisconsin Stone Quality of Life Questionnaire (WISQOL) to assess the relationship of stress to stone-related QOL in kidney stone patients. Methods: As part of the WISQOL Research Consortium, patients were approached in outpatient clinics and completed the WISQOL and the Perceived Stress Scale 10-item questionnaire (PSS-10). Patients with stones at enrollment were divided into those with symptoms and those without, while patients with no current stones formed another group. Questionnaire scores from each group were compared statistically and correlations between the groups were calculated. Results: Patients (n=704) were enrolled from six centers. The WISQOL successfully discriminated between patients with current stones and those without (p<0.0001), while the PSS-10 did not (p=0.0869). The PSS-10 revealed patients with symptomatic kidney stones experienced higher levels of general stress than asymptomatic subjects (p<0.0001). However, a Pearson correlation test comparing the responses from each instrument revealed no overall correlation between general stress and HRQOL (r=0.05). Conclusions: Symptomatic kidney stones increase general stress, as these patients demonstrate higher PSS-10 scores. Despite this, no correlation exists between general stress and stone-related QOL in patients with stone disease regardless of their stone and symptom status. This implies the existence of other factors impacting QOL in these patients, which warrants further exploration.